Economic security of regions: A methodological approach to assessment, management, and legal regulation - Ovcharenko, Ohla; Korotka, Larysa; Smiesova, Viktoriia; Kuchkova, Ohla; Karpenko, Roman (REGION, 2022)
At the present stage of development, one of the major problems of regions is ensuring their economic security. This requires the development of effective methodological approaches to assessing economic security at the regional level by governing bodies, and the development of directions for regulating economic security at the local and state levels. The purpose of the article is to form methodological tools for assessing the economic security of regions based on the method of fuzzy modeling, to develop approaches to managing the economic security of a region by public authorities and local governments. The article has proposed and analyzed indicators for assessing the economic security of regions. The expediency of using fuzzy logic tools to assess economic security at the meso-level has been substantiated. The effectiveness of the proposed approach has been tested on the example of Dnipropetrovsk, Odessa and Chernivtsi regions in Ukraine. The integral index of economic security has been modelled, together with its components: investment, innovation, financial, foreign economic, demographic, social security and security of economic activity. It has been empirically proven that the economic security of regions is determined not only by the resources available in the region, but also by the conditions created by the state and local governments for economic and innovation activities and for maintaining the level and quality of life, as well as institutional conditions. The article has proposed directions for economic and legal regulation of economic security in Ukraine, which are aimed at increasing the level of economic security in the depressed regions in Ukraine.